2008
DOI: 10.5194/aab-51-381-2008
|View full text |Cite
|
Sign up to set email alerts
|

Quality of goat meat from purebred French Alpine kids and Boer crossbreeds

Abstract: Abstract. Some quality traits of meat from purebred French Alpine kids and Boer crossbreeds aged 50 days were evaluated in the study. Samples of m. quadriceps femoris were taken to determine the chemical composition and physicochemical properties of meat as well as a water-to-protein ratio, energy value, levels of cholesterol and amino acids in protein, and fatty acid concentration in intramuscular fat. It was found that meat from crossbred kids, compared to meat from purebred kids, contained more intramuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
(21 reference statements)
5
18
0
Order By: Relevance
“…The proportions of the fatty acids were in the typical range for ruminants (Atti et al, 2006;Banskalieva et al, 2000;Bas et al, 2005;Beserra et al, 2004;Tshabalala et al, 2003). The results of this study are particularly consistent with data reported by Brzostowski et al (2008), where the same muscles considered herein (quadriceps femoris) were studied.…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…The proportions of the fatty acids were in the typical range for ruminants (Atti et al, 2006;Banskalieva et al, 2000;Bas et al, 2005;Beserra et al, 2004;Tshabalala et al, 2003). The results of this study are particularly consistent with data reported by Brzostowski et al (2008), where the same muscles considered herein (quadriceps femoris) were studied.…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…As a result of these differences, the IMF of meat from Anglo Nubian kids contained significantly less hypercholesterolemic acids (OFAs) and had a more desirable UFA/SFA ratio. In contrast, Brzostowski et al (2008) recorded that intramuscular fat of meat from French Alpine x Boer kids (meat type) contained significantly less SFA, and significantly more total PUFA, compared to the IMF of meat from French Alpine kids (dairy type); differences can be attributed to the feeding system (doe's milk vs doe's milk + meadow hay + concentrate) and the muscles considered (LT, ST and cuadriceps femoris). A significant effect of the genotype of goat kids on the fatty acid profile of IMF was also demonstrated by Beserra et al (2004).…”
Section: Resultsmentioning
confidence: 88%
“…The mean values of pH1 at the age of 90 and 180 days of life (6.00 vs. 6.03) and pH2 (5.66) were within a range (5.5-5.9) considered optimal for high-quality goat meat (STANISZ and GUT 2005, HEROLD et al 2007, BRZOSTOWSKI et al 2008. KESAVA RAO et al (2003) observed a decrease of pH2 to 5.71 after 24 h, whereas SEN et al (2003) obtained even lower pH2 value (5.48) in 5-to-6-month old goat kids.…”
Section: Discussionmentioning
confidence: 93%
“…The higher the protein content was the higher value of W/ B index obtained. Meat of French Alpine kids compared to meat of French Alpine × Boer crossbreed contained higher (P≤0.05) index W/P (4.18), and lower dry matter content (22.21 %) and crude protein content (19.44 %) (BRZOSTOWSKI et al 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation